PENGUATAN LITERASI BAHASA ARAB SANTRI MELALUI TRADISI LALARAN KITAB DI PESANTREN NADROTUL ULUM - Ahmad Tarikul Majid; Akmal Varras Amrulloh; Luthfiyatuz Zuhriyah (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to examine the strengthening of students’ Arabic literacy through the tradition of lalaran kitab at Pesantren Nadrotul Ulum. The background of this research is based on the importance of Arabic literacy as a fundamental skill in understanding classical Islamic texts (kitab kuning), as well as the challenges of learning in the modern era which demand more effective and contextual methods. This study employs a descriptive qualitative method with a field research approach. Data were collected through observation, interviews, and documentation involving the pesantren leader, teachers, and students as research subjects. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the lalaran kitab tradition plays a significant role in enhancing students’ Arabic literacy, particularly in improving reading fluency, understanding of linguistic structures, and gradual comprehension of textual meaning. This tradition also contributes to fostering discipline and a strong learning culture among students. However, the effectiveness of lalaran is influenced by its implementation methods, the role of teachers, and the variation of instructional approaches used. Therefore, it is necessary to optimize the lalaran kitab tradition through more systematic and innovative methods to address the challenges of learning in the modern era..